1979
DOI: 10.1055/s-0028-1092678
|View full text |Cite
|
Sign up to set email alerts
|

Serum T4T3and Reverse T3During Treatment with Propranolol in Hyperthyroidism, L-T4Treated Myxedema and in Normal Man

Abstract: Serum concentrations of T4, T3 and reverse T3 were studied in two hyperthyroid groups (n = 13 and 11), in a group of normals (n = 9) and in a group of L-T4 substituted patients (n = 7) with severe pretreatment hypothyroidism. Serum T4 did not change except in one of the hyperthyroid groups change to in which a slight decrease was found. In all groups a significant fall in serum T3 and a significant rise in serum reverse T3 were found. An expected increase in serum TSH in the normal and in the L-T4 substituted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Reported mean concentrations in the serum of healthy adults have been 8.7 ng/dL 55 and 2.6 ng/dL (range, 1.6 to 3.0 ng/dL or 26 to 48 pmol/L) 26 for T3A, and 28 ng/dL (range, <8 to 60 mg/dL or <105 to 800 pmol/L) for T4A. Serum T4A levels are reduced during fasting and in patients with severe illness, although the Antiinflammatory and immunosuppressive; decreases intracranial pressure Propranolol 441,442 Adrenergic blocker (antiarrhythmic, antihypertensive) Interleukin-6 443 Cancer therapy Iodinated contrast agents:…”
Section: Tetraiodothyroacetic Acid (Tetrac) and Triiodothyroacetic Acmentioning
confidence: 99%
“…Reported mean concentrations in the serum of healthy adults have been 8.7 ng/dL 55 and 2.6 ng/dL (range, 1.6 to 3.0 ng/dL or 26 to 48 pmol/L) 26 for T3A, and 28 ng/dL (range, <8 to 60 mg/dL or <105 to 800 pmol/L) for T4A. Serum T4A levels are reduced during fasting and in patients with severe illness, although the Antiinflammatory and immunosuppressive; decreases intracranial pressure Propranolol 441,442 Adrenergic blocker (antiarrhythmic, antihypertensive) Interleukin-6 443 Cancer therapy Iodinated contrast agents:…”
Section: Tetraiodothyroacetic Acid (Tetrac) and Triiodothyroacetic Acmentioning
confidence: 99%
“…the mechanism by which these drugs alleviate some of the clinical features of hyperthyroidism is uncertain. It has been shown that propranolol does not affect the release of T4 from the thyroid gland (Wartofsky et al, 1975) but causes a significant lowering of serum T3 with a concomitant rise in serum rT3 in normal subjects, hyperthyroid patients and hypothyroid patients made clinically euthyroid with thyroxine treatment (Verhoeven ef a/.. 1977;Feely eta/., 1979;Faber et al, 1979). These data have been interpreted by several workers as evidence that the effect of propranolol in hyperthyroidism may be mediated through the altered peripheral metabolism of thyroid hormones (Lotti eta/., 1977;Verhoeven et a/., 1977;Saunders et a/., 1978).…”
Section: Rcsir1tcmentioning
confidence: 99%
“…Recent studies suggest that propranolol may have an effect on peripheral thyroid hormone turnover. Thus Faber et al (3) and Kallner et al (6) demonstrated a decrease in serum triiodothyronine (T3) and a rise in reverse T3 (rT3) in serum from propranololtreated hyperthyroid patients.…”
mentioning
confidence: 98%